A quality of life study in patients with leprosy using DLQI and WHOQOL-BREF questionnaires - Dakshata A Tare; Vishalakshi Viswanath; Kalpita S Pai; Dinesh R Samel (Wolters Kluwer Medknow Publications, 2021)
Context: India accounts for 60% of the global leprosy burden. Deformities lead to a negative impact on the quality of life (QoL). There is a paucity of Indian studies evaluating the QoL in patients with leprosy. Aims: This study was undertaken to assess QoL in leprosy patients with two different questionnaires, correlate QoL with demographic and clinical profile and evaluate the impact on health-related QoL scores. Settings and Design: A cross-sectional study to evaluate the QoL was conducted in the dermatology OPD of a tertiary center in Maharashtra, India. Materials and Methods: Demographic and clinical profile along with evaluation of QoL using DLQI and WHOQOL-BREF questionnaires was conducted in 60 leprosy patients. Statistical Analysis Used: Parametric test, R test, Chi-square test, Z test, Student's t-test (t), and Pearson's correlation coefficient (r) were used. Results: The mean DLQI score was 8.4 ± 4.4 and 40% of patients had moderate impact on QoL, and the mean WHOQOL-BREF score was 3.13 ± 0.9. The demographic profile, type of leprosy and reactions did not have a statistically significant correlation with DLQI. Presence of deformity had significant impact on DLQI and a statistically significant impact on physical, psychological, and environmental domain in WHOQOL-BREF analysis. Conclusions: Deformities have a profound impact on QoL in leprosy patients on evaluation with DLQI and WHOQOL- BREF questionnaires. The social domain was least affected, whereas severe impact was noted in psychological domain. DLQI is a practical and simple questionnaire, whereas WHOQOL- BREF provides a comprehensive approach on all domains.